Materials challenges and testing for supply of energy and resources - Bollinghaus, Thomas (Springer Berlin Heidelberg, 2012)
One major goal of the World Materials Research Institute Forum - WMRIF is to promote young scientists in the field of materials science and engineering. To enhance the international knowledge exchange between young postdoctoral scientists all over the world, WMRIF meanwhile regularly organizes joint workshops among the member institutes. These workshops also represent an increasingly appreciated platform to get known to each other and to build co-operations. For such workshops, various topics are selected, pointing to future perspectives and challenges in the field of materials science and engineering. This time, the presentations of the workshop focused on the four subjects Challenges in conclusive, realistic and system oriented materials testing Materials challenges for water supply Materials challenges in the extraction and recovery of scarce elements and minerals Materials challenges for nuclear fission and fusion. This book comprises the peer-reviewed contributions during the 2nd International Workshop for Young Materials Scientists at BAM Federal Institute for Materials Research and Testing, Berlin, Germany. It also provides a very informative overview of recent results for all materials scientists.